Unusual Cause of Acute Scrotal Pain-Inflammatory Noncommunicating Hydrocele: A Pediatric Case Report. (8th February 2018) - Moritoki, Yoshinobu; Mizuno, Kentaro; Kato, Taiki; Yasui, Takahiro; Hayashi, Yutaro
Abstract : The etiology of scrotal pain is clinically classified in terms of the necessity for emergency surgery. Lately, color Doppler ultrasonography has reduced unnecessary surgeries, but there are still some cases that require immediate exploration because of an uncertain diagnosis. Here, we describe the case of a 14-month-old boy, who could not deliver his complaint accurately, presenting with a grumpy mood and a red swollen scrotum. Emergency surgery revealed that the cause was intense inflammation of the hydrocele wall, which typically does not cause acute scrotum. We also reviewed rare etiologies of scrotal pain for general physicians to develop the differential diagnosis.